TOWARDS A DETERMINATION OF DEFINITIVE PARAMETERS FOR THE LONG PERIOD CEPHEID S VULPECULAE - Turner, D. G. (Одеські астрономічні публікації, 2013)
A new compilation of UBV data for stars near the Cepheid S Vul incorporates BV observations from APASS and NOMAD to augment UBV observations published previously. A reddening analysis yields mean colour excesses and distance moduli for two main groups of stars in the field: the sparse cluster Turner1 and an anonymous background group of BA stars. The former appears to be 1.07 ± 0.12 kpc distant and reddened by EB−V =0.45 ± 0.05, with an age of 109 yrs. The previously overlooked latter group is 3.48 ± 0.19kpc distant and reddened by EB−V =0.78 ± 0.02,with an age of1.3 × 107 yrs. Parameters inferred for S Vul under the assumption that it belongs to the distant group, as also argued by 2MASS data, are all consistent with similar results for other cluster Cepheids and Cepheid-like supergiants.